FORMULASI NUTRASUTIKAL COKLAT (Theobroma cacao L.) DAN DAUN KATUK (Sauropus androgynus) SEBAGAI ASI BOOSTER - Ulyana, Dewi; Ratnasari, Hesti; Nikmah, Ilya Syafa’atun; Wijayanti, Rina (Media Farmasi Indonesia, 2019)
ASI (Mother's Milk) is a good source of nutrition for babies. One of the traditionalplants used to multiply and accelerate breastfeeding is katuk leaves. Katuk leaves have beenknown as traditional medicine efficacious as laktogogum or ASI enhancer (ASI). For thisreason, katuk leaves are made into a formulation of chocolate milk supplementation forbreast milk which is preferred by women. Objective: To determine the katuk leaf nutritionpreparation formula and the effectiveness of preparations as ASI (Mother's Milk). Method:This study used a one shot pre-experiment case study design with katuk leaf pollination andchocolate nutrition making, then tested the effectiveness of 10 panelists. The measurement ofASI volume is done 1 day before storing katuk leaf chocolate and the next 7 days afterconsuming katuk leaf chocolate. Results: The results of measurements of ASI volume wereanalyzed using the Mann Whitney test, where there were significant differences in ASI volumeor p <0.05. Conclusion: Chocolate nutaseutical product formulation from katuk leaves asenhancer for breast milk, ASI volume measurements were carried out for 1 days notconsuming katuk leaf chocolate and for 7 days consuming katuk chocolate leaves p <0.05 wassignificantly different. meaningless.